2022
DOI: 10.1099/acmi.0.000360
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19-Associated mucormycosis: Case series from a tertiary care hospital in South India

Abstract: The pandemic coronavirus disease 2019 (COVID-19) caused by severe acute respiratory syndrome coronavirus 2 (SARS-COV-2) is a global health problem. COVID-19 has given rise to a number of secondary bacterial or fungal infections. During the second wave of COVID-19, India experienced an epidemic of mucormycosis in COVID-19 patients. In this paper, we discuss the clinical features, investigations and management of four patients having COVID-19-associated mucormycosis (CAM), especially rhino-orbital mucormycosis (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…Sulis et al in their study on an interrupted time series analyses of sales volumes of antibiotics in India have estimated that 216.4 million excess doses of antibiotics, and 38.0 million excess doses of azithromycin were prescribed/used until the peak of the first pandemic wave[44].In this research work, 34 (73.91%) patients were diagnosed as positive by KOH mount wherein broad aseptate/pauciseptate ribbons such as hyphae with random wide-angle branching, sporangia, and rhizoids were seen. Direct microscopy by KOH expedites the early diagnosis of mucormycosis, thereby helping the treating doctors to initiate anti-fungal therapy at the incipient stages of infection[45,46]. Culture positivity was seen in 56.52% of the cases in this study, and lactophenol cotton blue (LPCB) mounts from the colonies revealed Rhizopus spp.…”
mentioning
confidence: 70%
“…Sulis et al in their study on an interrupted time series analyses of sales volumes of antibiotics in India have estimated that 216.4 million excess doses of antibiotics, and 38.0 million excess doses of azithromycin were prescribed/used until the peak of the first pandemic wave[44].In this research work, 34 (73.91%) patients were diagnosed as positive by KOH mount wherein broad aseptate/pauciseptate ribbons such as hyphae with random wide-angle branching, sporangia, and rhizoids were seen. Direct microscopy by KOH expedites the early diagnosis of mucormycosis, thereby helping the treating doctors to initiate anti-fungal therapy at the incipient stages of infection[45,46]. Culture positivity was seen in 56.52% of the cases in this study, and lactophenol cotton blue (LPCB) mounts from the colonies revealed Rhizopus spp.…”
mentioning
confidence: 70%
“…They can reduce allergic reactions, however, in combination with SARS-CoV-2 infection they can dysregulate the immune system and widely inhibit immune responses (26). Also, the hypoxia results in acidic pH and the generation of reactive oxygen species (ROS), which could lead to cellular deterioration and contribute to conditions favorable for mucormycosis proliferation (2). In our reviewed cases, the majority of the confirmed cutaneous mucormycosis in COVID-19 patients have been reported from India (14/27, 52%), followed by Egypt (4/27, 15%), USA (3/27, 11%), Iran (2/27, 7.4%), one case (1/27, 3.7%) each from Spain, Palestine, Romania and Iraq.…”
Section: Discussionmentioning
confidence: 99%
“…Coronavirus disease , a viral respiratory infection with a rapid global spread, has caused the death of more than four million people globally (1). Patients with underlying comorbidities accompanying COVID-19 are more susceptible to contracting secondary bacterial or fungal infections (2). Mucormycosis has been reported as a serious infection with an unprecedented rise among patients recovering from a recent SARS-CoV-2 disease.…”
Section: Introductionmentioning
confidence: 99%